PRODUKTIVITAS PENULIS ARTIKEL ILMIAH BIDANG ILMU INFORMASI DAN PERPUSTAKAAN PADA JURNAL TERAKREDITASI PERINGKAT SINTA 2, 3 DAN 4 TAHUN 2015-2019 - Sri Junandi; Dwiyantoro Dwiyantoro (Perpustakaan Nasional RI, 2021)
There are 15 scientific journals in the field of Library and Information Science (LIS) accredited and indexed by Science and Technology Index (SINTA). The journals are divided by rating namely SINTA 2 (4 journals), SINTA 3 (4 journals) and SINTA 4 (7 journals). This study aims to determine the productivity pattern of authors in the field of LIS in 2015 - 2019 indexed in SINTA 2, 3 and 4 based on Lotka's rules. The research approach is quantitative with bibliometric analysis. The results show that based on: (1) article published during 2015 – 2019, there were 1,806 authors with a frequency of article writing 1,061; (2) the calculation of the author's productivity pattern, shows the value of n = 0.93062 and the value of C = 0.74864; and (3) the K-S test results show that the Dmax value was greater than the critical value for SINTA 2 and 4, while for the SINTA 3 the Dmax value was smaller (0.0172) than the critical value (0.108).